HUBUNGAN ANTARA DAYA LEDAK OTOT BAHU DAN KEKUATAN GENGGAMAN TERHADAP KEMAMPUAN TOLAK PELURU GAYA MENYAMPING PADA SISWA PUTRA MTs NW KORLEKO - Izmul Pahmi; Jamaludin Jamaludin; Subakti Subakti (Universitas Pendidikan Mandalika, 2018)
The explosive force of the shoulder muscles and the strength of the grasp is a contributing factor in the ability of sideways force to decline in determining the repulsion of an athlete. Problems in this research are Lack of ability to sideways to turn sideways force on student of MTs NW korleko Lesson year 2016-2017. The formulation of the problem in this research is whether there is a correlation between the explosive force of the shoulder muscles and the strength of the grip on the ability of sideways styles tossing force on students of MTs MTs NW Korleko academic year 2016-2017